Papel do cortex pré-frontal medial no comportamento defensivo de camundongos : avaliação farmacológica da lateralização funcional - Costa, Nathália Santos (Universidade Federal de São Carlos, 2017)
Stressful situations are risk factors to the development of neuropsychiatric diseases, as anxiety disorders. However, not everyone who experiences stressful events develops stress-related illness. That is due to the existence of differences in the ability to adapt to stress, that is, the manifestation of susceptibility or resilience phenotypes. The search for understanding neural systems involved to these differences has evidenced an important role of the medial Prefrontal Cortex (mPFC), and, recently, its functional lateralization has been highlighted. In this sense, the right mPFC (RmPFC) seems to modulate anxiogenic-like responses, while the left mPFC (LmPFC) would attenuate such responses, thereby facilitating animals to cope with threatening situations. If so, LmPFC inhibition would intensify ansiogenic-like behavior front to aversive stimuli. Under this hypothesis, one of the goals of the present study was to investigate whether the inhibition of the LmPFC could modulate the effect of two types of stress (the restraint and the social defeat) on anxiety. Yet, we also aimed to investigate whether NMDA-glutamate receptor would be involved to the anxiogenic-like effect induced by nitrergic activation of the RmPFC, given the anxiogenic potential of glutamate and the interaction already known between these neurotransmissions. To reach that, experiments were carried out (1) to characterize the effects of social defeat and restraint stress on animals exposed to elevated plus maze (EPM) 5 minutes or 24 hours later; (2) to evaluate the effects of restraint or social defeat combined to the synaptic inactivation (through nonspecific inhibitor, CoCl2) of the LmPFC on the defensive behavior of mice exposed to EPM 24 h after stress; (3) to investigate the effects of NMDA receptor antagonism and (4) the effect of that antagonism on anxiogenic-like effects induced by NO donor. The results showed that both restraint and defeat stress are anxiogenic at 5 minutes, but defeated mice do not display anxiety 24 h after stress. Furthermore, the synaptic inhibition produced a clear anxiogenic-like effect in defeated (but not restrained) mice. In addition, the blockade of NMDA receptors produced anxiolytic-like effects and reversed the anxiogenic effect induced by NO injection into the RmPFC. Taken together, these results corroborate previous studies demonstrating the functional lateralization of the mPFC, in which the right and left hemispheres seem to have distinct roles in the modulation of aversive events.
Keywords: Ansiedade; Estresse; Lateralização funcional; Córtex pré-frontal; NO-Glutamato; Anxiety; Stress; Functional lateralization; Medial prefrontal cortex; NO-Glutamate; CIENCIAS BIOLOGICAS::FISIOLOGIA